A Panca Budi Charter-Based Organizational Culture Model for Strengthening Lecturers' Organizational Commitment and Organizational Citizenship Behavior - Nuraini Kemalasari Istiqamah; Hernawaty; Geby Citra Ananda (International Journal of Management, Economic and Accounting, 2026)
Organizational culture rooted in the philosophical values of a university's founding charter serves as an important foundation shaping the work behavior of academic staff, yet such values are often not operationally internalized into a tested model of their influence on lecturers' attitudes and behavior. This study aims to formulate and test a model of organizational culture based on the Panca Budi Charter in building organizational commitment and Organizational Citizenship Behavior (OCB) among lecturers. A quantitative explanatory survey approach was applied to permanent lecturers, with data analyzed using Partial Least Square Structural Equation Modeling (SEM-PLS). The results show that charter-based organizational culture has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on OCB, and organizational culture significantly affects OCB both directly and indirectly through organizational commitment as a partial mediating variable. These findings confirm that internalizing founding-charter values and strengthening organizational commitment must be pursued simultaneously to optimize lecturers' organizational citizenship behavior. This study contributes theoretically by proposing a charter-based organizational culture model and offers practical implications for human resource management in higher education institutions